2015
DOI: 10.4103/2230-8210.163187
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone and the risk of bladder cancer: An Indian retrospective cohort study

Abstract: Aim:To determine whether pioglitazone is associated with an increased risk of bladder cancer among Indian type 2 diabetic patients.Methods:A retrospective data analysis of 2222 type 2 diabetic patients was conducted. The study subjects were divided into two equal groups: 1111 pioglitazone users and 1111 pioglitazone non-users. The safety of pioglitazone therapy was analyzed in terms of occurrence of bladder and other types of cancers along with its efficacy in terms of glycemic control. Parameters for assessin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…In order to assess the cumulative effect of pioglitazone use and to determine whether there is an increased risk of urinary bladder cancer in case of prolonged use, we analyzed 12 studies using HR as the relative association measure [ 19 , 23 , 24 , 33 41 ]. Ten of them are cohort studies with two prospective cohort studies [ 23 , 33 ] and eight retrospective cohort studies [ 24 , 34 , 35 , 37 41 ]. There is one observational study [ 19 ] and one case–control study [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to assess the cumulative effect of pioglitazone use and to determine whether there is an increased risk of urinary bladder cancer in case of prolonged use, we analyzed 12 studies using HR as the relative association measure [ 19 , 23 , 24 , 33 41 ]. Ten of them are cohort studies with two prospective cohort studies [ 23 , 33 ] and eight retrospective cohort studies [ 24 , 34 , 35 , 37 41 ]. There is one observational study [ 19 ] and one case–control study [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…An Indian retrospective cohort study aimed to determine whether pioglitazone is associated with an increased risk of bladder cancer and analyzed 2222 patients divided into two equal groups. It is interesting to point out that there was no evidence of bladder cancer in any of the studied groups [ 35 ]. The study by Lee et al [ 37 ] investigated the factors that may link pioglitazone to bladder cancer among 34,970 subjects identified from the National Health Insurance Research Database.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, few studies reported no risk of bladder cancer with pioglitazone use [10,11]. For instance, a recent population based cohort study conducted in United Kingdom (UK) generated 689,616 person years of follow-up, during which 622 patients were newly diagnosed as having bladder cancer (crude incidence 90.2 per 100,000 person years).…”
Section: Reviewmentioning
confidence: 99%
“…15 Conversely, a recent retrospective cohort study conducted in India documented that pioglitazone was not associated with the bladder cancer in the T2DM patients. 16 Drug Technical Advisory Board (DTAB) of India in 2013 recommended deferment of pioglitazone or manufacture and sale of pioglitazone containing formulation be withdrawn and allowed to be marketed with special caution. 17 Limited real world data regarding safety concern of pioglitazone use and risk of bladder cancer are equivocal and unknown.…”
Section: Introductionmentioning
confidence: 99%